Preparation, evaluation, and in vitro cytotoxicity studies of artesunate-loaded glycyrrhetinic acid decorated PEG-PLGA nanoparticles. (1st November 2020) - Pan, Xuwang; Liu, Shourong; Ju, Liping; Xi, Jianjun; He, Ruoyu; Zhao, Yanmei; Zhuang, Rangxiao; Huang, Jinsong
Abstract: Objective: The objective of this study was to prepare the liver targeting drug delivery system (TDDS) of artesunate (ART)-loaded polyethylene glycol (PEG)-poly(d, l -lactic-co-glycolic) acid (PLGA) nanoparticles (NPs) modified by glycyrrhetinic acid (GA), and evaluate its in vitro cytotoxicity. Significance: The GA-PEG-PLGA-ART NPs enhanced the in vitro cytotoxicity on HCC cell lines. The development of GA-PEG-PLGA NPs will greatly push the clinical applications of ART as a novel anticancer drug. Methods: The NPs were prepared using solvent evaporation method, and the formulation was optimized through an orthogonal design. In addition, physical properties were determined, including particle size, polydispersity index (PDI), zeta potential (ZP), morphology, drug loading capacity (LC) and encapsulation efficiency (EE), and in vitro drug release. Moreover, the in vitro cytotoxicity of NPs with three human cancer cell lines viz. HepG2, Hep3B, and SMCC-7721 was conducted using the SRB assay. Additionally, lyophilization was conducted to improve the long-term physical stability. Results: The GA-PEG-PLGA-ART NPs have spherical shape, small particle size (around 88 nm) with a narrow size distribution (PDI < 0.3), high drug LC (up to 59.3 ± 1.65%), and high EE (up to 73.13 ± 5.17%). In vitro drug release behavior showed that drugs were released from NPs in a sustained and controlled release pattern. Cytotoxicity study indicated the NPs achieved lower cancer cell survival fraction. The GA-PEG-PLGA NPs freeze-dried with 3% (w/v) of mannitol showed better effect on long-term physical stability. Conclusion: The GA-PEG-PLGA-ART NPs appear as a potential liver targeted intracellular delivery platform for ART.